The impact of COVID-19 on the work of property valuers: A glance at the Polish state of play - Małgorzata Uhruska; Agnieszka Małkowska (Journal of Risk and Financial Management, 2021)
This article presents how the COVID-19 pandemic affected the valuation profession in Poland in the early stages of its most severe restrictions and limitations. This study is the first to investigate the impact of COVID-19 on the professional activities of property valuers. In particular, it aims to identify the difficulties associated with valuers' activities during the first lockdown and the impact of restrictions on business performance. The data analyzed come from a survey of Polish valuers in September 2020. The questions were of a closed-ended nature. Using a five-point Likert scale, respondents expressed their opinions on the difficulties and benefits of their work in the first COVID-19 period. The results show that the respondents experienced difficulties related to the pandemic and noted its negative impact on business performance. The most significant problem was the limited access to public institutions supporting the valuation process and providing market data on real estate transactions. The respondents also indicated other problems related to property valuation, as well as some positive effects for their business.
Keywords: 330; COVID-19 pandemic; COVID-19 impact; property valuation; property valuation business; property valuer; real estate services